Development of Teaching Module Based on Independent Learning to Optimize Students' Conceptual Knowledge on the Motion Topic - Amna Abdullah; Mursalin; Muhammad Yusuf; Trisnawaty Junus Buhungo; Supartin (Jurnal Penelitian Pendidikan IPA, 2025)
Teaching modules are independent curriculum bodies which replace learning plans. This study aims to development of teaching module based on independent learning to optimize students’ conceptual knowledge on the motion topic. The development of teaching modules using the ADDIE model consists of five stages: analysis, design, development, and implementation. This research used 15 class VII students as teachers at SMP Negeri 3 Satap Tabongo. Based on the validation results from three validators, the average percentage for the teaching module was 81.25%, which was in the very valid category and suitable for use in learning the motion topic. Based on the practicality of the Independent Curriculum-Based Teaching Module to optimize students' conceptual knowledge, it meets the practicality criteria with a score of 93.18% for teachers and student activities of 91.67%.and the results of the student responses were very good. Based on the effectiveness of the Independent Curriculum Based Teaching Module to optimize students' conceptual knowledge, it meets the criteria for effectiveness.